2014
DOI: 10.1186/1471-2350-15-46
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CDH23 mutations in Korean families with hearing loss by whole-exome sequencing

Abstract: BackgroundPatient genetic heterogeneity renders it difficult to discover disease-cause genes. Whole-exome sequencing is a powerful new strategy that can be used to this end. The purpose of the present study was to identify a hitherto unknown mutation causing autosomal recessive nonsyndromic hearing loss (ARNSHL) in Korean families.MethodsWe performed whole-exome sequencing in 16 individuals from 13 unrelated small families with ARNSHL. After filtering out population-specific polymorphisms, we focused on known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
(23 reference statements)
2
24
0
Order By: Relevance
“…In a Japanese study, CDH23 mutations were reported to be frequent after GJB 2 and SLC26A4 in children and adults with hearing impairment [6]. Recently, CDH23 mutations have been reported in the Korean deaf population [7, 8], and genetic loads of CDH23 and its implications in the Korean pediatric population have also recently been reported [9]. Accordingly, p.P240L in CDH23 proved to exert a strong founder effect in the Korean pediatric population with severe-to-profound nonsyndromic SNHL.…”
Section: Introductionmentioning
confidence: 99%
“…In a Japanese study, CDH23 mutations were reported to be frequent after GJB 2 and SLC26A4 in children and adults with hearing impairment [6]. Recently, CDH23 mutations have been reported in the Korean deaf population [7, 8], and genetic loads of CDH23 and its implications in the Korean pediatric population have also recently been reported [9]. Accordingly, p.P240L in CDH23 proved to exert a strong founder effect in the Korean pediatric population with severe-to-profound nonsyndromic SNHL.…”
Section: Introductionmentioning
confidence: 99%
“…A homozygous c.5985C > A (p.Y1995X) variant, a heterozygous p.E1006K, and p.D1663V were detected in the Chinese population [47,48]. The mutation frequency spectrum of CDH23 among the recessive inherited cases is 5.7% in the Japanese population and 15% in the Korean population [16,19,49]. Other gene variants were also analyzed using such programs such as V66 M variant of human BDNF in psychiatric disorders and computational modeling of complete HOXB13 protein for predicting the functional effect of SNPs and the associated role in hereditary prostate cancer [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…It accounted for up to 32% of Usher syndrome type 1 cases [13]. More than 24 associated mutations have been reported as missense mutations that clearly appeared as an important cause of hearing loss in Asian populations [16][17][18][19]. Recent research studies suggest that in silico mutation prediction might be used as a first-line molecular diagnosis tool serving both genetic counseling and mutation verification and variant classification [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to ARHGEF40 and BRD9, the function of CDH23 has not been established hitherto [47] in spite of being implicated in Usher syndrome type ID and non-syndromic hearing loss [50]. CDH23 belongs to the cadherin family, a family that mediates calcium-dependent cell adhesion [51]. Here, CDH23 was associated with biologic processes, such as the positive regulation of cytosolic calcium, regulation of cytosolic ion concentration, and cellular calcium ion homeostasis.…”
Section: Discussionmentioning
confidence: 99%